Proselytizer Motivation and Awareness Who be Aware of Communication Technology in the Building Relations and Preach to Community - Santa Lorita Simamora (Nusantara Science and Technology Proceedings)
One of the strongest impact of globalization is the fast growing of communication technology. The characteristic of technology communication is interactive and dynamic. It makes technology communication has a crucial role in human’s life. One of its role is in the spreading process of religion preaching. Technology information allows us to make a wide networking. So, it minimizes distance among message sender and the receiver. Besides that, it also allows us to spread the information to a lot of places directly. Preaching is the activity to tell people about Islam. By the time, the method of preaching has been changing from traditional to be more modern by using technology. If traditional method still focuses on door to door preaching that is through mosques, modern method is more variation by combining door to door method and social media. It is because most Muslim in Indonesia has already used social media. The focus of this research is how to use social media such as facebook, whatsapp, instagram, and TV streaming as preaching media and how to build the relationship with the pilgrims.The goal of this research is to depict the lecturer’s ability to use facebook, whatsapp, and instagram as preaching media and build the relationship with his/her pilgrims.This research uses qualitative approach, constructivist paradigm, and case study method. The researcher collect the data through observation, deep interview, and documentation study. The collected data is analyzed using descriptive qualitative model by Miles and Huberman that referring to inductive data analysis.Based on the analysis process, the result shows that preaching through social media is able to reach more pilgrims, even though they come from different places and has not met before. Another result is preaching through social media is also can build a strong enough relation between the lecturer and his/ her pilgrims. From this result, the researcher suggests to all lecturer to start using social media as preaching media.